Molecular Characterization of Carbapenem-Resistant Enterobacter cloacae in 11 Chinese Cities - Jin, Chunmei; Zhang, Jiangang; Wang, Qi; Chen, Hongbin; Wang, Xiaojuan; Zhang, Yawei; Wang, Hui (Frontiers in Microbiology, 2018)
Carbapenem-resistant Enterobacteriaceae are usually resistant to most of antibiotics. Infections caused by such bacteria have a high mortality and pose a serious threat to clinical management and public health. Enterobacter cloacae ranks third among Enterobacteriaceae that cause nosocomial infections. In this study, the molecular characteristics of carbapenem-resistant Enterobacter cloacae in China were investigated. From November 2012 to August 2016, 55 non-repetitive strains of carbapenem-resistant Enterobacter cloacae were collected from 12 hospitals in 11 Chinese cities. The bacteria were identified with matrix-assisted laser desorption/ionization time of flight mass spectrometry. Antimicrobial susceptibility tests were determined by agar dilution method. Carbapenemase and other β-lactamase genes were detected with PCR and sequencing. Multilocus sequence typing and plasmid conjugation tests were performed. Among the 55 Enterobacter cloacae strains, 50 strains were detected to produce 8 types of carbapenemase including NDM-1, NDM-5, IMP-4, IMP-26, IMP-1, KPC-2 and VIM-1. NDM-1 accounted for 68.0% (34/50) among the carbapenemase-producing Enterobacter cloacae. A total of 24 sequence types were identified and ST418 was the most common, accounting for 20% (11/55). For further investigation, a pulsed-field gel electrophoresis (PFGE) assay was conducted to identify the PFGE patterns of the strains. These 23 isolates yielded 13 PFGE patterns, which were designated as type A to M. Eight isolates obtained from Shenzhen had the same PFGE pattern (type A) and the remaining 15 isolates belonged to the other 12 PFGE patterns (type B to M). The observation that 8 of the 15 blaNDM-1-positive E. cloacae isolates obtained from Shenzhen with the same PFGE pattern (type A) suggested a transmission outbreak of a common strain. S1-nuclease PFGE and Southern blotting were also conducted to estimate the size of plasmids harbored by blaNDM-1-positive strains. The results showed that the plasmids harboring the blaNDM-1 gene ranged in size from approximately 52 to 58 kilobases. Our study indicates that carbapenem-resistant Enterobacter cloacae strains that produce NDM carbapenemase have strong resistance. Early detection and monitoring of the prevalence of these strains are urgent.